Utilização de sistemas de informação geográfica na identificação de áreas vulneráveis à contaminação do lençol freático : o caso da bacia do alto e médio curso do rio Uberabinha - MG - Costa, Felipe Provenzale Mariano (2009)
Due to the necessity of finding an efficient way of management for the water resources, the drainage basin has been proposed as the basic unity for its planning and management. As mentioned, it has been chosen the basin portion of the Uberabinha River situated in the city of Uberlandia as the area to be studied. As the drainage basin of the Uberabinha River has suffering a strong agricultural occupation in the last decades, and constitutes the water source responsible for the water supplies of the city of Uberlandia., the present assignment propose to analyze the aspects regarding as soil types and its usage and occupation, utilizing procedures of analyses and evaluation that gives an understanding of the infiltration aspects of the water in each unity of the soil regarding its natural coverage and developed cattle raising activities. Such statement is justified as the tendencies of modern agriculture for major productivities is highly high-tech and dependable of agricultural input, as the use of some elements in those production systems produce pollution, characterized by the low concentration of contaminants throughout very extended areas ( punctual or diffuse). As the quantity and the state of the conditions that influence on the characteristics of the impacts on a fluvial basin by anthrop actions are innumerous, the adoption of the Geographic Information Systems (GIS) as the main tool is needed. Determinates GIS s software were used (SPRING 5.0.1 and ARCGIS 9.2) with the intention to identify areas vulnerable to the contamination of the superficial and sub superficial water by agricultural defensives, taking in consideration the usage of the soil, data from water infiltration gotten from a research made in situ using the Guelph permeameter, type of soil, declivity and depth of the water table. With that, the results obtained were hydraulic conductivity, the potential infiltration and vulnerability of contamination. It was used the resources available on the software ARCGIS 9.2, more specific the Raster Calculator tool available on the Spatial Analyst extension software, to be able to achieve the desired results on operations like the algebra of maps. The SPRING software was used to process the satellite images from Landsat 5 satellite, to be able to do the mapping of the usage of the soil. The survey of the hydraulic conductivity for types of soils specified, it was important to see the relation that exist between the management of developed cattle raising activities and the percolation of the pluvial water, as been perceptively the difference between the areas that still maintains its natural coverage and the areas that still has the anthrop activities continuing. The potential infiltration map represents an important tool to identify the areas with major risk of erosion, as been the headwater course and the slope of the fluvial valleys with major declivity. The vulnerability map of water contamination represented the areas where the water source presented with major level of probability of being contaminated by residues followed upon yearly harvest, via sub superficial water and superficial water.